2018
DOI: 10.1523/jneurosci.1898-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglia Are Particularly Vulnerable to Oxidative Damage after Neurotrauma In Vivo

Abstract: Loss of function following injury to the CNS is worsened by secondary degeneration of neurons and glia surrounding the injury and is initiated by oxidative damage. However, it is not yet known which cellular populations and structures are most vulnerable to oxidative damage Using Nanoscale secondary ion mass spectrometry (NanoSIMS), oxidative damage was semiquantified within cellular subpopulations and structures of optic nerve vulnerable to secondary degeneration, following a partial transection of the optic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 67 publications
0
69
0
Order By: Relevance
“…Many studies have used this model [4][5][6][7][8][9][10][11][12][13] . In these previous studies, PONT in rats was administrated from the superior side of optic nerves; however, in this study we cut the optic nerves from the temporal side and found that this operation was much easier to conduct than from the superior side due to the lack of obstruction from rectus superior and obliquus superior eye muscles ( Fig.…”
Section: Glaucoma and Partial Optic Nerve Transection Modelmentioning
confidence: 99%
“…Many studies have used this model [4][5][6][7][8][9][10][11][12][13] . In these previous studies, PONT in rats was administrated from the superior side of optic nerves; however, in this study we cut the optic nerves from the temporal side and found that this operation was much easier to conduct than from the superior side due to the lack of obstruction from rectus superior and obliquus superior eye muscles ( Fig.…”
Section: Glaucoma and Partial Optic Nerve Transection Modelmentioning
confidence: 99%
“…The secondary phase of injury involves a cascade of ischemia, inflammation, and cell death including, and of importance in this review, oligodendrocytes (Crowe, Bresnahan, Shuman, Masters, & Beattie, 1997;Hilton, Moulson, & Tetzlaff, 2017;Kwon, Tetzlaff, Grauer, Beiner, & Vaccaro, 2004;Norenberg, Smith, & Marcillo, 2004). Oligodendrocytes are susceptive to damage from reactive oxygen species, excitotoxicity, extracellular ATP, and pro-inflammatory cytokines all of which are present following SCI (Crowe et al, 1997;Giacci et al, 2018;Plemel et al, 2014). Preclinical data show that as the milieu of the spinal cord becomes less toxic (Crowe et al, 1997;Williams et al, 2014), a period of remyelination follows (Blight, 1985;Hesp, Goldstein, Miranda, Kaspar, & McTigue, 2015;Powers et al, 2012).…”
mentioning
confidence: 99%
“…3 However, the numbers of EdU-negative oligodendrocytes did not decrease until 28 days after injury. 3 It is a possibility that the numbers of these cells were reduced at 14 days after injury; however, this was not assessed.…”
Section: Oligodendroglial Vulnerability To Secondary Degenerationmentioning
confidence: 96%
“…The opportunity to explore using NanoSIMS allowed direct comparison between cellular subpopulations and structures in the context of secondary degeneration in vivo for the first time and provided direct evidence that OPCs and oligodendroglia are the most vulnerable, when compared with other cellular subpopulations and structures in the CNS. 3 …”
Section: Oligodendroglial Vulnerability To Secondary Degenerationmentioning
confidence: 99%